Urinary TIMP‐2 and MMP‐2 are significantly associated with poor bladder compliance in adult patients with spina bifida. Issue 8 (4th September 2019) - Peyronnet, Benoit; Richard, Claire; Bendavid, Claude; Naudet, Florian; Hascoet, Juliette; Brochard, Charlène; Senal, Nelly; Jezequel, Magali; Alimi, Quentin; Khene, Zine‐eddine; Corlu, Anne; Clément, Bruno; et al.
Abstract: Aims: To assess the predictive values of six urinary markers (nerve growth factor [NGF], brain‐derived neurotrophic factor [BDNF], matrix metalloproteinase 2 [MMP‐2], tissue inhibitor metalloproteinase 2 [TIMP‐2], transformation growth factor β‐1 [TGF‐B1], and prostaglandin 2 [PGE2]) for adverse urodynamic features and for upper urinary tract damage in adult patients with spina bifida. Materials and methods: A single‐center prospective trial was conducted from March 2015 to March 2017 including all consecutive adult patients with spina bifida seen for urodynamic testing. The urine was collected and stored at −80°C. A urodynamic and an upper urinary tract were systematically performed. At the end of the inclusion period, urines were defrosted and urinary nerve growth factor, BDNF, TIMP‐2, and TGF‐B1 were assessed using validated ELISA kits. The urinary markers levels were adjusted on the urinary creatinine level. Urinary MMP‐2 levels were assessed by zymography. Results: Fourty patients were included. Only TIMP‐2 and MMP‐2 were significantly associated with poor bladder compliance ( P = .043 and P = .039, respectively). TIMP‐2 was also the only urinary marker significantly associated with upper urinary tract damage on imaging (OR = 19.81; P = .02). Of all urodynamic parameters, bladder compliance and maximum detrusor pressure were the only ones associated with upper urinary tract damage on imaging ( P = .01 and P = .02), The diagnostic performances of urinary TIMP‐2 for upper urinary tract damage were slightly superior to PdetMax and bladder compliance with an area under the curve of 0.72. Conclusion: Urinary TIMP‐2 and MMP‐2 were significantly associated with poor bladder compliance and urinary TIMP‐2 was significantly associated with upper urinary tract damage. These findings support a pathophysiological role of extracellular matrix remodeling in poor bladder compliance of adult patients with spina bifida.